JUSTIFICATION OF WIDTH OF THE TAPE OF THE MILL OF THE FEEDER MILLING-ROTORY SNOW BLOWER - D. S. Aleshkov; N. Y. Ayupova (Вестник СибАДИ, 2017)
In article the question of influence of number of calling of a mill of a feeder of a millingrotary snow blower on volume of the cut-out snow prism is considered. Also the equation of definition of dependence of width of a tape of a mill on a mill angle of rotation has been received. Results of calculations of change of width of a tape of a mill and change of the transported volume of a snow prism on schedules are presented. Images of mills with a width of the tape providing compliance to height of the figure limiting the cut-out volume of snow weight are submitted.